SURGICAL TREATMENT OF POST-BURN SCARS OF NECK AND CHEST - A.H. SHAYMONOV; G.M. KHODZHAMURADOV; M.M. ISMOILOV; M.S. SAIDOV (Avicenna Tajik State Medical University, 2017)
Objective: To study the frequency of application of various types of skin flaps in patients with consequences of extensive burns of the neck and chest area. Methods: The experience of surgical treatment of the consequences of burns in the neck and chest area was studied in 17 patients with extensive lesions. All patients underwent excision of scar-modified tissue, with the subsequent covering of the formed defect with free or non-free flaps from other anatomical zones. Surgical treatment was performed only with hypertrophic scars; the presence of keloid scars was the criterion for excluding the patient from the study group. Results: The use of non-free flaps yielded the best results due to aesthetic acceptability and coverage of large defects in the covering tissues of the neck and chest region. Full-thickness dermal grafts taken from the inguinal region, as well as from various areas of the upper limb, showed themselves to be more aesthetically justified, but their use allowed them to cover only defects of small and medium size. Despite the fact that the use of different types of non-free flaps allowed to cover defects of large sizes, the aesthetic result of their application in seven patients (41.2%) was relatively satisfactory, in view of the extensive lesions and residual consequences. Conclusion: With defects in the neck of small and medium sizes, the use of free and non-free flaps is justified and has an optimal aesthetic result. Further research should be aimed at finding new varieties of flaps with minimal donor damage or other means of cover in cases of extensive post-burn defects in other anatomical areas involving potential donor zones